2019
DOI: 10.1080/20905068.2019.1658340
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference and hip circumference as potential predictors of visceral fat estimate among type 2 diabetic patients at the Komfo Anokye Teaching Hospital (KATH), Kumasi-Ghana

Abstract: Background: Although visceral fat (VF) and its influence on cardiovascular diseases have been extensively studied among diabetic patients, there is a need for an easier, and less expensive but equally good predictor for VF. This study was conducted to assess potential anthropometric measurements that can be directly linked to visceral fat levels among diabetic patients. Method: 405 diabetic patients attending the Diabetic clinic of the Komfo Anokye Teaching Hospital (KATH) in Kumasi-Ghana were recruited. A wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 60 publications
(55 reference statements)
4
17
1
Order By: Relevance
“…Compared to BMI indicators, the prevalence of obesity based on WC and WHR indicators was 0.9% and 0.4% higher respectively. This is consistent with the findings by several cross-sectional studies [23,24,25] who observed a higher prevalence of obesity when WC and/or WHR were used as obesity measures compared to BMI. This confirms the evidence that increased WC is a stronger indicator of obesity risk compared to BMI [23,26].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to BMI indicators, the prevalence of obesity based on WC and WHR indicators was 0.9% and 0.4% higher respectively. This is consistent with the findings by several cross-sectional studies [23,24,25] who observed a higher prevalence of obesity when WC and/or WHR were used as obesity measures compared to BMI. This confirms the evidence that increased WC is a stronger indicator of obesity risk compared to BMI [23,26].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings by several cross-sectional studies [23,24,25] who observed a higher prevalence of obesity when WC and/or WHR were used as obesity measures compared to BMI. This confirms the evidence that increased WC is a stronger indicator of obesity risk compared to BMI [23,26]. BMI is currently been considered as an insufficient measure of obesity as it does not correctly identify individuals with excess body fat due to its inability to differentiate fat and fat-free mass and it does not account for the effect of age and ethnicity on body fat distribution [27].…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic patients usually possess greater quantities of visceral, subcutaneous, total, and intermuscular adipose tissues than healthy people 1 4 . Studies have found an association between high VF and cardiovascular diseases, insulin resistance, dyslipidemia and glucose intolerance in diabetic patients 2 , 3 , 5 . This predisposes diabetic patients to several diabetes complications, metabolic abnormalities, and cardiometabolic diseases 2 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found an association between high VF and cardiovascular diseases, insulin resistance, dyslipidemia and glucose intolerance in diabetic patients 2 , 3 , 5 . This predisposes diabetic patients to several diabetes complications, metabolic abnormalities, and cardiometabolic diseases 2 4 , 6 . Based on these findings, it has become necessary to assess an individual’s body composition, particularly percentages of fat and muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation